God, the mind's desire : reference, reason and Christian thinking - Janz, Paul D. (Cambridge studies in Christian doctrine ;, 2004)
'How can human discourse refer meaningfully to a transcendent God?' Paul Janz's book reconfigures this fundamental problem of Christian thinking as a twofold demand for integrity: integrity of reason and integrity of transcendence. It culminates in a convergence within Christology and epistemology within empirical reality.